Adiponectin overexpression improves metabolic abnormalities caused by acid ceramidase deficiency but does not prolong lifespan in a mouse model of Farber Disease - Marie K. Norris; Trevor S. Tippetts; Joseph L. Wilkerson; Rebekah J. Nicholson; J. Alan Maschek; Thierry Levade; Jeffrey A. Medin; Scott A. Summers; William L. Holland (Molecular Genetics and Metabolism Reports, 2024)
Farber Disease is a debilitating and lethal childhood disease of ceramide accumulation caused by acid ceramidase deficiency. The potent induction of a ligand-gated neutral ceramidase activity promoted by adiponectin may provide sufficient lowering of ceramides to allow for the treatment of Farber Disease. In vitro, adiponectin or adiponectin receptor agonist treatments lowered total ceramide concentrations in human fibroblasts from a patient with Farber Disease. However, adiponectin overexpression in a Farber Disease mouse model did not improve lifespan or immune infiltration. Intriguingly, mice heterozygous for the Farber Disease mutation were more prone to glucose intolerance and insulin resistance when fed a high-fat diet, and adiponectin overexpression protected from these metabolic perturbations. These studies suggest that adiponectin evokes a ceramidase activity that is not reliant on the functional expression of acid ceramidase, but indicates that additional strategies are required to ameliorate outcomes of Farber Disease.